An example of entrepreneurship in rural areas: socio-economic analysis of livestock enterprises supported by the expert hands project - Satar, Muharrem; Arıkan, Mehmet Saltuk; Peker, Arzu (My University, 2022)
This study was carried out in order to reveal the socio-economic structure of the enterprises that implement the cattle and small cattle breeding project within the scope of the expert hands project implemented as a pilot in 4 provinces in Turkey, their perspectives on the project implementation and the sustainability of the projects. Within the expert hands project scope, 50 entrepreneurs benefited from the livestock project. Within the area of the research, data were collected from the entrepreneurs of 36 projects, 18 small ruminant, and 18 cattle, in Turkey, using the Google survey tool. It has been determined that 47.2% of the entrepreneurs have worked in another job before. 61.1% of the entrepreneurs stated that they will continue their livestock activities. 24% of business owners meet their financing needs by providing loans. It has been determined that 24 of the entrepreneurs do not have any income other than animal husbandry. The capacity utilization rate was calculated as 58.6% on average. The fact that 61.1% of the entrepreneurs want to continue the project shows that the interest of young people in the sector is still high. It is thought that there is an opportunity for those who want to start their own business in rural areas despite having received sufficient training in the field within the scope of the project. Implementation of the project in all provinces will bring a new dynamism to the rural area and contribute to the sustainability of animal production with entrepreneurs trained in the sector.
Keywords: Turkey; Entrepreneurship; livestock enterprises; socio-economic; expert hends project